Cultural Nuances and Marital Intimacy: Exploring Sexual Fantasies, Communication, and Personality in Indonesian Couples - Charli Sitinjak (Bulletin of Counseling and Psychotherapy)
Marriage satisfaction is a complex interplay of various factors, encompassing sexual dynamics, communication patterns, and individual personality traits. However, within the cultural context of Indonesia, empirical research examining these dynamics is notably scarce. This study endeavors to fill this void by delving into the intricate relationships among sexual imagination, communication styles, personality traits, and marital satisfaction among 254 married individuals in Indonesia. Employing a cross-sectional design, data were gathered through online surveys utilizing validated instruments, including the International Index of Erectile Function, the Female Sexual Function Index, the Sexual Daydreaming Scale, the Dyadic Sexual Communication Scale, and the Interpersonal Exchange Model of Sexual Satisfaction Questionnaire. Through statistical analysis, the study unveils compelling insights into the dynamics shaping marital contentment in the Indonesian context. The findings illuminate a nuanced landscape: a negative correlation emerges between sexual fantasies and marital satisfaction, indicating a potential tension between individual fantasies and conjugal fulfillment. Conversely, positive correlations are observed between effective sexual communication and certain personality traits (such as openness and empathy) with marital satisfaction, emphasizing the pivotal role of transparent dialogue and interpersonal qualities in fostering marital harmony. These findings hold significant implications for marital counseling and intervention strategies tailored to the Indonesian cultural context. By acknowledging and addressing the nuanced dynamics of sexual imagination, communication, and personality traits within marriages, practitioners can better support the well-being of married couples in Indonesia, ultimately contributing to stronger and more fulfilling marital relationships..